?OCCURRENCE OF FISH EGGS (FAMILIES: ENGRAULIDAE AND CARA GIDAE) IN THE BACKW ATER OF KARACHI HARBOUR (Biological Sciences - PJSIR, 1998)
Fishes of the I'amilies Engraulidac and Carangidac are known to breed all along the coastline of Pakistan and their eggs and larvae drift in the mangrove areas. During the 13 months or sampling lrorn Dec. 1992 -Dec. 1l)93, a total or 2979 fish eggs were collected from the mangrove area along the Karachi habour, 47 fish eggs bel nged to families Engrnulidac and Carangidac. These eggs were separated in three genera: Tlirissocles, /snchoviella and Caranx, The study reports distribution and occurrence of eggs and their detail description.